Characterization of molecular composition of bacterial melanin isolated from streptomyces glaucescens using ultra-high-resolution FT-ICR mass spectrometry - Choi, Mira; Choi, A. Young; Ahn, Soo Yeon; Choi, Kwon Young; Jang, Kyoung Soon (Mass Spectrometry Letters, 2018)
In this study, the chemical composition of bacterial melanin isolated from the Streptomyces glaucescens strain was elucidated by ultra-high-resolution Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry. Ultra-high-resolution mass profiles of the microbial melanin product were acquired using a 15 Tesla FT-ICR mass spectrometer in positive and negative ion modes via electrospray ionization to obtain more complete descriptions of the molecular compositions of melanin-derived organic constituents. A mass resolving power of 500,000 (at m/z 400) was achieved for all spectra while collecting 400 scans per sample with a 4 M transient. The results of this analysis revealed that the melanin pigment isolated from S. glaucescens predominantly exhibits CHON and CHO species, which belong to the proteins class of compounds, with the mean C/O and C/N ratios of 4.3 and 13.1, thus suggesting that the melanin could be eumelanin. This analytical approach could be utilized to investigate the molecular compositions of a variety of natural or synthetic melanins. The compositional features of melanins are important for understanding their formation mechanisms and physico-chemical properties.
Keywords: Chemical composition; Eumelanin; FT-ICR MS; Melanin; Streptomyces glaucescens